Late gadolinium enhancement is a strong predictor of life threatening arrhythmias in patients with dilated cardiomyopathy undergoing ICD implantation for primary prevention of sudden cardiac death. (3rd October 2022) - Lopes Da Cunha, G J; Lopes, P; Freitas, P; Rocha, B; Gomes, D; Paiva, M; Amador, R; Abecasis, J; Guerreiro, S; Matos, D; Rodrigues, G; Carvalho, M S; et al.
Abstract: Background: The usefulness of implantable cardioverter defibrillators (ICD) for primary prevention of arrhythmic sudden cardiac death (SCD) in patients with non-ischemic dilated cardiomyopathy (DCM) has been questioned. Efforts to improve risk stratification have included scores such as the "MADIT-ICD benefit score", and the use of late gadolinium enhancement (LGE) in cardiac magnetic resonance (CMR). The purpose of this study was to evaluate the potential usefulness of these two tools to assess the risk of life-threatening arrhythmias in patients with non-ischemic DCM undergoing ICD implantation for primary prevention of SCD. Methods: We conducted a single-center retrospective study of consecutive patients who underwent contrast-enhanced CMR before ICD implantation for primary prevention of SCD. Patients with ischemic cardiomyopathy were used as reference. Patients with non-dilated cardiomyopathies were excluded. The arrhythmic component of the MADIT-ICD benefit score (VT/VF score) was calculated for each patient, and considered high if ≥7, as recommended. The primary endpoint was the occurrence of SCD or life-threatening arrhythmias (VF or VT >200 bpm). Follow-up was performed by device interrogation in all patients except those who suffered SCD. Results: A total of 151 patients (93 ischemic, mean age 62±13 years, 75% male) with mean left ventricular ejection fraction (LVEF) of 27±8% were included. Overall, 72% (n=67) ischemic and 45% (n=26) non-ischemic patients had scores ≥7 and were considered high-risk. LGE was present in all patients with ischemic cardiomyopathy, and in 76% (n=44) of patients with non-ischemic DCM. During a median follow-up of 21 (8–38) months, 21 patients (13.9%, 11 ischemic and 10 non-ischemic) met the primary endpoint. Overall, the event-free survival of non-ischemic patients was similar to that of ischemic patients (log rank p=0.269). In patients with non-ischemic DCM, there were 7 arrhythmic events (26.9%) in those with MADIT-ICD VT/VF scores ≥7, and 3 events (9.4%) in those with scores <7 (log rank p=0.104). In the same population, there were 10 arrhythmic events (23%) in patients with LGE, but no events in patients without LGE (log rank p=0.036). LVEF was similar in patients with and without arrhythmic events (26±8% vs. 27±7%, p=0.717), and in those with and without LGE (26±7% vs. 28±9%, p=0.342). Conclusion: The presence of LGE is a strong predictor of life threatening arrhythmias in patients in non-ischemic DCM undergoing ICD implantation for primary prevention, seemingly outperforming the clinical MADIT-ICD benefit score. Funding Acknowledgement: Type of funding sources: None.